Changing Scenario of Nutritional Availability in Ballia District: A Geographical Overview - Kumar, Santosh; Singh, M.B. (National Geographical Journal of India, 2022)
Calories, protein, carbohydrates, minerals, vitamins, fats and water are essential nutrients for the growth of human body and its maintenance. Energy (Kcals) requirement of an individual is expressed as the total calories to be obtained from the food every day. It is supplied by carbohydrates, proteins and lipids of food. Protein is an important nutrient for the formation of regulatory compounds. Some hormones, all enzymes, and most other regulatory materials in the body are protein substances. Protein defends the human body against diseases. Protein is needed for building, maintaining and repairing body tissues. It is essential for body growth, especially for the young. The main nutritional role of carbohydrates is the production of energy. Each gram of food carbohydrate yields 4 Kcals of energy on oxidation in the body. Carbohydrates are t more suitable for the production of the energy in the body than proteins and fats, because carbohydrate molecules contain relatively more oxygen than others. Nutrition and health is one of the most appreciated aims of developing countries to be solved on priority basis. Land is the main and the most traditional source, which provides nutrition directly or indirectly to the people. The main objective of this study is to point out the spatiotemporal variations of nutritional availability in the study area during study period.